Effects of growth hormone-replacement therapy in patients with Prader-Willi syndrome - review of recent clinical trials - Michał Piwoński; Klaudia Żak; Marta Kozłowska; Bartłomiej Zaremba; Joanna Milanowska (Kazimierz Wielki University, 2020)
Introduction and objective: Prader-Willi syndrome (PWS) is a severe genetic disorder being manifested by several symptoms such as infantile hypotonia and poor thriving outcomes, low height, hyperphagia, endocrine, reproductive and internal malfunctions and malformations. In the disease treatment, growth hormone (GH)-replacement therapy is commonly carried on. In this article, we sum up the latest clinical trials' results concerning the effectiveness and safety of GH-replacement therapy. Abbreviated description of the state of knowledge: Taking into consideration six clinical trials performed in the years 2019-2020, most of them showed positive results of GH-replacement therapy in PWS patients, not only in case of better motor skills or body composition, but also concerning their social and adaptive functioning. Moreover, as for the cessation of GH treatment, some authors seem to highlight no deterioration in cognitive functioning in patients who attained adult height after GH-treatment. Summary: GH-replacement therapy seems to be a good therapeutic option for PWS-affected individuals. Nonetheless, in our research we did not come across on any clinical trials with more than one-year-long observations. Thus, on the long term, these results can not exclude a gradual deterioration of cognitive functioning.